QUANTITATIVE EASING AS THE MAIN INSTRUMENT OF UNCONVENTIONAL MONETARY POLICY - Halyna Alekseievska; Anzor Mumladze (Three Seas Economic Journal, 2020)
After the fall of Lehman Brothers in September 2008, the financial crisis turned into a global crisis and had a negative impact on the real economy. During the crisis, there has been a significant decrease in key macroeconomic indicators, such as GDP, short-term interest rates, unemployment and inflation. The GDP growth rate had taken a negative value in developed countries. Inflation was below 1 percent, and deflation was observed in Japan, which in turn slowed down economic development. Central banks responded to the crisis with a change in interest rates, but this was not enough to calm financial markets and improve the real economy. Most central banks have developed many new monetary policy tools, including communication strategies, credit policies, and large asset purchases. These new measures are often called “unconventional” monetary policies. The purpose of the article is to study quantitative easing as one of the unconventional measures of monetary policy. Methodology. The article uses general scientific and special methods: generalization, systematization, economic and statistical analysis, graphic and comparison methods. This allowed us to study the theoretical foundations of the quantitative easing policy, determine the economic background for these measures application, analyze the development stages and the basic rules of functioning policy. The quantitative easing policies usage was also examined on the examples of the Federal Reserve, the European Central Bank, the Bank of England and the Bank of Japan. Results. The main trends and economic conditions, under which these methods can be used in future, were identified using an analysis of the quantitative easing application background. The policy’s main components analysis provides a clear understanding of the quantitative easing essence. As a result of the unconventional monetary policy usage, there has been a significant expansion of the USA, Japan and the Eurozone central banks' balances, which amounts to more than 10 trillion USD. Due to this process, central banks have become key bondholders. Practical meaning. The given results analysis will determine that kind of unconventional monetary policy effectiveness and the possible consequences of a significant increase in the central banks’ balance sheet assets. Value/originality. In the article, the conditions, under which unconventional monetary policy has been applied, are systematized and the four central banks’ quantitative easing policy is compared.